Application and mechanism analysis of functionalized ionic liquids in copper regeneration from electroplating sludge. (15th April 2023) - Li, Feng; Xu, Xiaoxun; Cao, Chenchen; Yang, Zhanbiao; Wang, Guiyin; Li, Ting; Pu, Yulin; Zhang, Shirong; Cheng, Zhang; Lv, Guochun; Xu, Changlian; Xian, Junren; et al.
Abstract: Hydrometallurgy is the main method to regenerate valuable metals from electroplating sludge and reduce its environmental hazards. As a key step to efficiently recover metals, it is important to choose an environmentally friendly and efficient leaching agent. In this work, four green ionic liquid (ILs) ([BMIm]HSO4, [HOOCMIm]HSO4, [BSO3 HMIm]HSO4, and [BSO3 ]Py.HSO4 ) were used to leach copper from copper–rich electroplating sludge (C–ES). The tested ILs could effectively leach copper from C–ES, but functionalized ILs have better leaching efficiency, especially sulfonate ILs, which could remove 100% of Cu from C–ES under optimal conditions. Kinetics studies showed that the leaching process of controlled by chemical reaction and material diffusion, and the apparent activation energies were 39.21, 0.98, 14.47, and 41.93 kJ mol −1, respectively. Introducing functional groups (such as carboxyl and sulfonate group) which can complex with metals on cations can enhance the H + release and complexation ability of ILs, improve the mass transfer efficiency between liquid–solid phase, and thus improve the copper leaching ability by ILs. These findings are of great significance for selecting functional ILs to efficiently regenerate copper and the resource utilization from C–ES. Graphical abstract: Image 1 Highlights: An efficient leaching method of copper from electroplating sludge is proposed. The leaching behavior and the leaching mechanism of copper in ILs was analysed. Functionalized ILs had better hydrogen release and metal complexation ability. Sulfonate functionalized ILs is most conducive to copper recovery from C-ES.